Molière baroque : « définir contre » ? - Carol Clark (Etudes Epistémè)
« Molière, Baroque »? Not so long ago, this statement itself might have seemed « baroque », in the sense the word would have had in the period. To make of Molière, the great Classical author, the spokesman for French values par excellence (reason, clarity, common sense) a Baroque author would have seemed extravagant, even anti-Republican. But in the course of the twentieth century, the term « Baroque » has been redefined, and after René Bray, a whole series of critis have read Molière more as a dramatic author than as a moral author. This paper will study some aspects of Molière’s dramatic art which can, in our opinion, be considered as appertaining to the « Baroque », in particular his use of framing devices and the playful spirit found both in his court entertainments and his comedies written for the town.